MARKETING ASSISTANCE THROUGH PACKAGING TRAINING FOR HOME INDUSTRY PRODUCTS TO DEVELOP POTENTIAL MSMES IN COT MESJID VILLAGE, BANDA ACEH - Murni, Mirza; Fuad, Ammar; Husni, Almira Sabrina; Parsi, Siti Noviana (Universitas Muhammadiyah Aceh, 2024)
The development of trade and business today is highly dependent on electronic commercial transactions or what is called e-commerce online with various digital business applications that do offer many choices and conveniences so that competition is very tight. This requires business actors to be ready to compete in the digitalization era that requires the ability to run an online business. The demands of today's era are greatly influenced by clear and accurate information in making decisions and determining actions that must be taken to develop and maintain a business. Aceh Besar is a very strategic area and has many MSME actors whose numbers continue to increase every year. Kuta Cot Glie District is a district included in the Aceh Besar Regency area and also has many MSME actors spread across every village in the district. However, many MSME actors in Kuta Cot Glie District have not taken advantage of the opportunities from the development of information technology in marketing their products due to the low quality of human resources in the field of technology and information. Digital marketing is the application of digital technology that contributes to marketing activities that aim to gain profit by expanding market share and building and developing relationships with customers. Of course, this can also be utilized by MSMEs in marketing their products online, including MSMEs in villages in Kuta Cot Glie sub-district, Aceh Besar Regency.Keywords : Digital Marketing, E-Commerce, Digital Business Applications